2000
DOI: 10.1093/glycob/10.10.1013
|View full text |Cite
|
Sign up to set email alerts
|

The type and yield of lipopolysaccharide from symbiotically deficient Rhizobium lipopolysaccharide mutants vary depending on the extraction method

Abstract: At least 18 lipopolysaccharide (LPS) extraction methods are available, and no single method is universally applicable. Here, the LPSs from four R.etli, one R.leguminosarum bv. trifolii mutant, 24AR, and the R.etli parent strain, CE3, were isolated by hot phenol/water (phi;/W), and phenol/EDTA/triethylamine (phi/EDTA/TEA) extraction. The LPS in various preparations was quantified, analyzed by deoxycholate polyacrylamide gel electrophoresis (DOC-PAGE), and by immunoblotting. These rhizobia normally have two prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…The LPS extracted into the phenol phase was treated as described by Carrion et al (23). The LPS was purified from these crude preparations with affinity chromatography using polymyxin B-Sepharose (Pierce) (24,25). Briefly, the crude LPS was dissolved in 50 mM NH 4 CO 3 and applied to the column.…”
Section: Methodsmentioning
confidence: 99%
“…The LPS extracted into the phenol phase was treated as described by Carrion et al (23). The LPS was purified from these crude preparations with affinity chromatography using polymyxin B-Sepharose (Pierce) (24,25). Briefly, the crude LPS was dissolved in 50 mM NH 4 CO 3 and applied to the column.…”
Section: Methodsmentioning
confidence: 99%
“…LPS extraction and purification. The wild-type and mutant LPSs were first extracted by the TEA/EDTA/ procedure as previously described (43). For each strain, the bacterial pellet (approximately 10 g wet weight) from 8 liters of culture was extracted with 40 ml of TEA/EDTA/ (0.25 M EDTA containing 5% phenol and titrated to pH 6.9 with triethylamine [TEA]) with constant stirring at 37°C for 1 h. The extract was then centrifuged at 10,000 rpm for 1 h, and the supernatant was collected and dialyzed (2,000 molecular weight cutoff; Spectrapor) against deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…For each strain, the bacterial pellet (approximately 10 g wet weight) from 8 liters of culture was extracted with 40 ml of TEA/EDTA/ (0.25 M EDTA containing 5% phenol and titrated to pH 6.9 with triethylamine [TEA]) with constant stirring at 37°C for 1 h. The extract was then centrifuged at 10,000 rpm for 1 h, and the supernatant was collected and dialyzed (2,000 molecular weight cutoff; Spectrapor) against deionized water. This material was further purified by polymyxin affinity chromatography with polymyxin B-Sepharose (Pierce Chemical Company) as previously described (20,43,46). Briefly, after sample application in 50 mM NH 4 HCO 3 , the column (10-ml bed volume) was sequentially eluted with 30 ml of a solution of 0.3 M TEA adjusted to pH 6.4 with acetic acid plus 10% ethylene glycol, followed by 30 ml of a solution of 2.0 M urea in 0.1 M NH 4 HCO 3 to elute the non-LPS components.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study has shown that the ability to visualize polysaccharide alterations in bacterial mutants is often dependent upon the method used for extraction and analysis (Ridley et al, 2000). The polysaccharides isolated into the aqueous and the phenol phases were then resolved by DOC-PAGE and treated with either periodate or alcian blue followed by silver staining.…”
mentioning
confidence: 99%